Differential associations of allergic disease genetic variants with developmental profiles of eczema, wheeze and rhinitis. Issue 11 (15th October 2019) - Clark, Hannah; Granell, Raquel; Curtin, John A.; Belgrave, Danielle; Simpson, Angela; Murray, Clare; Henderson, A. John; Custovic, Adnan; Paternoster, Lavinia
Abstract: Background: Allergic diseases (eczema, wheeze and rhinitis) in children often present as heterogeneous phenotypes. Understanding genetic associations of specific patterns of symptoms might facilitate understanding of the underlying biological mechanisms. Objective: To examine associations between allergic disease‐related variants identified in a recent genome‐wide association study and latent classes of allergic diseases (LCADs) in two population‐based birth cohorts. Methods: Eight previously defined LCADs between birth and 11 years: "No disease, " "Atopic march, " "Persistent eczema and wheeze, " "Persistent eczema with later‐onset rhinitis, " "Persistent wheeze with later‐onset rhinitis, " "Transient wheeze, " "Eczema only" and "Rhinitis only" were used as the study outcome. Weighted multinomial logistic regression was used to estimate associations between 135 SNPs (and a polygenic risk score, PRS) and LCADs among 6345 individuals from The Avon Longitudinal Study of Parents and Children (ALSPAC). Heterogeneity across LCADs was assessed before and after Bonferroni correction. Results were replicated in Manchester Asthma and Allergy Study (MAAS) (n = 896) and pooled in a meta‐analysis. Results: We found strong evidence for differential genetic associations across the LCADs; pooled PRS heterogeneity P ‐value = 3.3 × 10 −14, excluding "no disease" class. The associations between the PRS and LCADs in MAAS were remarkably similar to ALSPAC. Two SNPs (a protein‐truncating variant in FLG and a SNP within an intron of GSDMB ) had evidence for differential association (pooled P ‐values ≤ 0.006). The FLG locus was differentially associated across LCADs that included eczema, with stronger associations for LCADs with comorbid wheeze and rhinitis. The GSDMB locus in contrast was equally associated across LCADs that included wheeze. Conclusions and clinical relevance: We have shown complex, but distinct patterns of genetic associations with LCADs, suggesting that heterogeneous mechanisms underlie individual disease trajectories. Establishing the combination of allergic diseases with which each genetic variant is associated may inform therapeutic development and/or predictive modelling.